Becoming to Being Filipino: A Social History of Music in Manila 1860-1940 through Journalistic Print - Silvestre, Ma. Patricia Brillantes; Jose, Ricardo Trota (Quezon City Asian Center, University of the Philippines Diliman, 2021)
This study traces and examines the process of the "becoming" to the "being" of the Filipinos as a people through music as written about in journalistic print in two succeeding colonial time frames in Manila: 1860 to 1899, the period of becoming in which a burgeoning sense of 'Filipino-ness' or an emergent nationalism was seen, and 1900 to 1940, the period of being in which the aspiration for a national state and its concomitant acts of defining, interrogating and appraising this 'Filipino-ness' were seen. This process of self-articulation is viewed as a continuum in which the first phase is active, shifting, restless-identity in a state of flux, and the second phase is seen as anchored and quasi-settled, where identity is established and particularized to a certain point yet contemplative, questioning and seeking definition n. Each phase unfolds vis-a-vis each time frame's unique socio-political conditions as mirrored or played out in the social space of a newspaper, which is also examined as a capitalist cultural object whose various music texts open up to multiple, alternate, even oppositional readings. These diverse music texts ranging from advertisements, images, song texts and scores to reviews, narratives and essays were culled from selected newspapers and periodicals from several archives. Through the agency of the press and its acts of production and consumption -writing, reading, viewing and hearing the nation, these texts are seen to have contributed immensely towards propagating an "imagined community" (Anderson 1991) in an expanded "public sphere" (Habermas), and must be viewed as crucial, dynamic chronicles of, as well as elements in, the birth and consolidation of the 'Filipino' and his music.
Thesis (Doctor of Philosophy in Philippine Studies)--University of the Philippines Diliman
Keywords: Music -- Social history -- Philippines